Effect of tetrabutylammonium iodide content on PVDF-PMMA polymer blend electrolytes for dye-sensitized solar cells - Theerthagiri, J.; Senthil, R.A.; Buraidah, M.H.; Madhavan, J.; Arof, Abdul Kariem (Springer Verlag (Germany), 2015)
The influence of tetrabutylammonium iodide on the polyvinylidene fluoride-poly(methyl methacrylate)-ethylene carbonate (PVDF-PMMA-EC)-I2 polymer blend electrolytes was investigated and optimized for use in a dye-sensitized solar cell. The different weight ratios (50, 60, 70, and 80 %) of tetrabutylammonium iodide (TBAI)-added PVDF-PMMA-EC-I2 polymer electrolytes were prepared. The prepared solid polymer blend electrolytes were characterized by using various techniques such as Fourier transform infrared (FT-IR) spectroscopy, differential scanning calorimetry (DSC), and electrochemical impedance spectroscopy (EIS). The FT-IR spectra revealed the interaction among all composition of polymer electrolytes. The influence of TBAI salt on the ionic conductivity of polymer electrolytes was studied using electrochemical impedance spectroscopy. The polymer electrolyte containing 60 % of TBAI in PVDF-PMMA-EC-I2 showed the highest room temperature conductivity of 5.10 × 10−3 S cm−1. The fabricated DSSC using PVDF-PMMA-EC-I2 polymer electrolytes with 60 % of TBAI showed the best performance with a short-circuit current density of 8.0 mA cm−2, open-circuit voltage of 0.66 V, fill factor of 0.65, and the overall power conversion efficiency of 3.45 % under an illumination of 100 mW cm−2. Hence, the weight content of organic iodide salt in polymer electrolytes influences the overall performance of dye-sensitized solar cells.